Pengaruh Akupresur Acupoint Payudara Titik CV 17 dan ST 18 Terhadap Waktu Pengeluaran ASI Pada Ibu Menyusui : The Effect of Acupressure on Breast Acupoints CV 17 and ST 18 on Breastmilk Ejection Time in Breastfeeding Mothers - Rusliani, Dian Monalisa; Navelia, Zesika Intan; Dewi , Novita Puspita (Journal of Health (JoH), 2024)
Exclusive Breastmilk is given at the babies’ age 0-6 months, it is the best food for babies can’t be replaced by any food and drink, and it’s given until 2 years old of babies. Some problem the can obstructed the breastfeeding process, such as the time current of breast milk. It may overdue of oxytocin and prolactin hormone. One example to stimulate and incase the breastmilk time production are acupressure. CV 17 and ST 18 are the dots of acupressure can increase the production of breastmilk. This research means to determine the effectiveness of acupressure breast acupoint on CV 17 ang ST 18 for time production of breastmilk in breastfeeding mother. The method of this research is true experiment one control post-test design with, the sample is 44 breastfeeding mother which have problem with late production of breastmilk chosen by purposive sampling.